Quantitative and sensitive RNA based detection of Bacillus spores - Osmekhina, Ekaterina; Shvetsova, Antonia; Ruottinen, Maria; Neubauer, Peter (Frontiers in Microbiology, 2014)
The fast and reliable detection of bacterial spores is of great importance and still remains a challenge. Here we describe a direct RNA based diagnostic method for the specific detection of viable bacterial spores which does not depends on an enzymatic amplification step and therefore is directly appropriate for quantification. The procedure includes the following steps: (i) heat activation of spores, (ii) germination and enrichment cultivation, (iii) cell lysis, and (iv) analysis of 16S rRNA in crude cell lysates using a sandwich hybridization assay. The sensitivity of the method is dependent on the cultivation time and the detection limit; it is possible to detect 10 spores per ml when the RNA analysis is performed after 6 h of enrichment cultivation. At spore concentrations above 106 spores per ml the cultivation time can be shortened to 30 min. Total analysis times are in the range of 2 to 8 hours depending on the spore concentration in samples. The developed procedure is optimized at the example of Bacillus subtilis spores but should be applicable to other organisms. The new method can easily be modified for other target RNAs and is suitable for specific detection of spores from known groups of organisms.